Ответы и объяснения

  • Участник Знаний
2013-04-21T19:20:05+00:00

(2x-3)^2=(x+5)^2

4x^2-12x+9=x^2+10x+25

4x^2-x^2-12x-10x+9-25=0

3x^2-22x-16=0

     11+-√121+48

x=---------------------

                3

    11+-13

x=-----------

          3

x=8

x=-2/3

Ответ: 8, -2/3

 

2013-04-21T23:58:06+00:00

(2x-3)^2=(x+5)^2

4x^2-12x+9-(x+5)^2=0

4x^2-12x+9-(x^2+10x+25)=0

4x^2-12x+9-x^2-10x-25=0

3x^2-12x+9-10x-25=0

3x^2-22x+9-25=0

3x^2-22x-16=0

D=(-22)^2-4*3*(-16)=484+192=676

x1=48/6=8
x2=-4/6=-2/3 (~-0.667)